CONVENTIONAL REFERENCE SERVICES: A SURVEY OF COLLEGE LIBRARIES IN CHANDRAPUR DISTRICT, MAHARASHTRA - Rokade , Shrikant S.; Sable, Sanjay N. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The main purpose of this survey was to comprehend the conventional information services offered in college libraries of Chandrapur district, Maharashtra, particularly reference services, availability of initial facilities, modes of providing reference services, barriers and solutions. A mini survey was conducted, and a virtual method was adopted. It was found that overall, 61% of aided and 42% of non-aided college libraries were engaged in providing conventional information services to their users. Unaided libraries provide fewer informational services than aided college libraries. All these libraries were found to provide (100%) conventional reference services. 68% of the basic facilities for the provision of reference services were provided in aided college libraries and 43% in unaided libraries. There were different modes to provide reference services in the library. 61% mode to provide reference services in an aided library and 43% unaided. Efforts should be made to offer information services to tribal communities to enhance traditional handicrafts, woodworking practices, and skills as a social commitment. Infrastructure, collection development, inadequate human resources and financial assistance, policy of government for filling of vacant posts, library space, and the impact of changing technology, maintenance and differentiations were the main barriers. There is a dire need to remove this barrier for the development of library information services in the interest of users and nations.